This preview shows pages 1–7. Sign up to view the full content.
This preview has intentionally blurred sections. Sign up to view the full version.
View Full DocumentThis preview has intentionally blurred sections. Sign up to view the full version.
View Full DocumentThis preview has intentionally blurred sections. Sign up to view the full version.
View Full Document
Unformatted text preview: Examine equations for type of solution Notice that the x and y directions are cou pled together, and the z direction is not coupled to either. If you look at the z equation first, youll see that it can be solved by a function whose second derivative is the negative of itself, i.e., sines and cosines. Really a linear com bination. Then we just need to solve for the coeffi cients in terms of initial conditions. L. Healy ENAE404 Spring 2007 Lecture 19 (Apr. 5) 1 Solve for z motion As noted, z is decoupled from the other direc tions. It is a simple harmonic oscillator. Set the coefficients correctly to match initial con ditions, z ( t ) = z cos nt + z n sin nt. L. Healy ENAE404 Spring 2007 Lecture 19 (Apr. 5) 2 Solve for x motion Take the x equation x = 2 n y + 3 n 2 x and differentiate once x (3) = 2 n y + 3 n 2 x, then substitute the y equation y = 2 n x x (3) = 4 n 2 x + 3 n 2 x, or x (3) + n 2 x = 0 . This should be recognizable as the simple har monic oscillator in v = x : v + n 2 v = 0 . L. Healy ENAE404 Spring 2007 Lecture 19 (Apr. 5) 3 Solve for v Harmonic oscillator solution v ( t ) = v x cos nt + v y sin nt is the most general, which means that the so lution for x is the integral x ( t ) = Z v ( t ) dt = x + v x n sin nt v y n (cos nt 1) . L. Healy ENAE404 Spring 2007 Lecture 19 (Apr. 5) 4 x and derivatives initial conditions All that remains is to find the constants, which we shall do by looking at x and its derivatives at t = 0, x (0) = x x ( t ) = v x cos nt + v y sin nt x (0) = x = v x x ( t ) = nv x sin nt + nv y cos nt x (0) = x = nv y so we have solved for v x and v y in terms of the initial x and derivatives, v x = x , v y = x n = 2 y + 3 nx where we substitute x = 2 n y + 3 n 2 x from the original differential equation. Thus x ( t ) = 4 x + 2 y n + x n sin nt 2 y n + 3 x cos nt. L. Healy ENAE404 Spring 2007 Lecture 19 (Apr. 5) 5 y solution Note that y equation depends on x and vice versa, so we can substitute our solution for x ( t ) y = 2 n x = 2 n x cos nt + x n sin nt = 2 n x cos nt (4 n y + 6 n 2 x )sin nt....
View Full
Document
 Spring '11

Click to edit the document details